Angela Merkel's discourse about the past: Implications for the construction of collective memory in Germany. (December 2019) - Yoder, Jennifer A
This article examines German Chancellor Angela Merkel's political discourse about the past. Through analysis of 54 of Merkel's speeches over a 10-year period, I explore when and how she references the past and whether she links the past to particular foreign policy choices. I suggest that Merkel draws upon several pasts—from different points in time and from different configurations of Germany—to present an integrated collective memory for a unified Germany.